Why caution is recommended with post‐hoc individual patient matching for estimation of treatment effect in parallel‐group randomized controlled trials: The case of acute stroke trials. (12th June 2013) - Jafari, Nahid; Hearne, John; Churilov, Leonid
<x xml:space="preserve">Abstract</x> A post‐hoc individual patient matching procedure was recently proposed within the context of parallel group randomized clinical trials (RCTs) as a method for estimating treatment effect. In this paper, we consider a post‐hoc individual patient matching problem within a parallel group RCT as a multi‐objective decision‐making problem focussing on the trade‐off between the quality of individual matches and the overall percentage of matching. Using acute stroke trials as a context, we utilize exact optimization and simulation techniques to investigate a complex relationship between the overall percentage of individual post‐hoc matching, the size of the respective RCT, and the quality of matching on variables highly prognostic for a good functional outcome after stroke, as well as the dispersion in these variables. It is empirically confirmed that a high percentage of individual post‐hoc matching can only be achieved when the differences in prognostic baseline variables between individually matched subjects within the same pair are sufficiently large and that the unmatched subjects are qualitatively different to the matched ones. It is concluded that the post‐hoc individual matching as a technique for treatment effect estimation in parallel‐group RCTs should be exercised with caution because of its propensity to introduce significant bias and reduce validity. If used with appropriate caution and thorough evaluation, this approach can complement other viable alternative approaches for estimating the treatment effect. Copyright © 2013 John Wiley & Sons, Ltd.